Las ciencias experimentales y la enseñanza bilingüe - Aragón, Mª.M. (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2017)
El dominio de las lenguas extranjeras, competencia esencial para la sociedad del siglo XXI, es una de las finalidades de los proyectos educativos actuales, de ahí el gran impulso que está cobrando la enseñanza bilingüe. La inclusión de las ciencias experimentales en los proyectos de bilingüismo, además de mejorar las competencias lingüísticas, puede favorecer el aprendizaje de las ciencias. Palabras clave: enseñanza de las ciencias; enseñanza bilingüe; discurso científico; habilidades cognitivo lingüísticas; actitudes. Experimental sciences and bilingual education A good knowledge of languages, an essential competence in this 21 th century society, is one of the target of the current curricula. The previous statement justifies that the bilingual teaching is increasing. The fact of including the experimental science in the bilingual projects would improve the linguistic competences and the science learning. Keywords: science teaching; bilingual teaching; scientific speech; linguistic and cognitive abilities; attitude.